2016
DOI: 10.7717/peerj.2722
|View full text |Cite
|
Sign up to set email alerts
|

Predictor effect of Locus Of Control (LOC) on self-care activities and metabolic control in individuals with type 2 diabetes

Abstract: BackgroundPrevious studies have examined the role of individuals’ personal characteristics in diabetes management and used the locus of control theory to assess adherence to a diabetes management regimen. These studies have emphasized that having internal locus of control may be a protective factor in diabetes management.ObjectiveThe purpose of this study is to determine the predictor effect of locus of control on self-care activities and A1c level.MethodThe study is descriptive and relational. Researchers use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
3
0
3
Order By: Relevance
“…The self-care behavior that is still not fully carried out 7 days a week is also found in a study by Kusniawati (2011), it was found that the average diabetes self-care activities were 4.9 days a week. Likewise, research by Besen et al (2016) on 129 people with type 2 diabetes mellitus in Turkey showed the frequency of self-care activities in the past week was 2.9 days. Self-care behavior that is not done properly will cause increased glucose levels.…”
Section: Self-care Behaviormentioning
confidence: 98%
“…The self-care behavior that is still not fully carried out 7 days a week is also found in a study by Kusniawati (2011), it was found that the average diabetes self-care activities were 4.9 days a week. Likewise, research by Besen et al (2016) on 129 people with type 2 diabetes mellitus in Turkey showed the frequency of self-care activities in the past week was 2.9 days. Self-care behavior that is not done properly will cause increased glucose levels.…”
Section: Self-care Behaviormentioning
confidence: 98%
“…Penelitian ini menggunakan metode penelitian literature review yakni sebuah jenis penelitian yang sistematis dan eksplisit yang berupaya memeriksa, menganalisa, mengevaluasi, dan mensintesiskan berbagai temuan penelitian, teori, dan bahan penelitian lainnya terkait dengan topik tertentuguna menemukan ruang kosong bagi penelitian selanjutnya (Efron & Ravid, 2018) (Al Nawafa'h & Hamdan-Mansour, 2015;Octari et al, 2020). Individu dengan HLoC internal juga percaya bahwa mereka memiliki kendali atas situasi yang mereka hadapi (Besen et al, 2016). Penelitian lain menyebut bahwa penyandang DM yang memiliki HLoC eksternal yang baik akan berpengaruh pada kualitas hidup yang lebih baik (Octari et al, 2020;Williams et al, 2016).…”
Section: Metode Penelitianunclassified
“…Penyandang DM yang patuh terhadap makanan, berolahraga, perawatan kaki, pengobatan dan pemantauan glukosa darah memiliki internal HLOC yang tinggi.Kepatuhan terhadap terapi farmakologis lebih tinggi daripada berolahraga dan penyandang DM mengakui pentingnya menemui dokter mereka secara teratur dan mengikuti rekomendasi mereka untuk mengendalikan Diabetes mereka (Williams et al, 2016). Selain itu, kelompok yang menggunakan insulin memiliki internal HLOC yang lebih besar (Besen et al, 2016).…”
Section: Perilaku Penyandang Dm Terhadap Hlocunclassified
See 1 more Smart Citation
“…Locus of health control, a multifaceted construct, can also affect adherence to treatment regimens in diabetes (Büyükkaya, Günüşen, Sürücü, & Koşar, 2016 ; O’Hea et al, 2009 ; Schlenk & Hart, 1984 ). This refers to the individuals’ perceptions of who or what controls their health within several domains including internal control, chance and powerful others (Wallston, Wallston, Kaplan, & Maides, 1976 ).…”
Section: Introductionmentioning
confidence: 99%